THREE-CHAMBER FURNACE FOR BURNING UP PEAT MIXTURES WITH WOOD WASTE - Shikhabutinova, O. (Енергетика і автоматика, 2016)
Results of investigations of the combustion process of low–grade fuels such as peat, wood waste and its mixtures in the low–power heat generator has been given. It has been found that the burning process quality is substantially affected by the fuel composition and mixing the wood waste to the peat. It has been found that the rational organization of the aerodynamics of the combustion chamber has improved the combustion process not only in relation to the decrease in emissions of nitrogen oxides, but also carbon oxide and, in some cases, the addition of 50% wood waste has reduced the amount of harmful emissions by half.